THE IDEOLOGY OF POPULAR CULTURE IN ESTI KINASIH’S 'FAIRISH' - Ellita Permata Widjayanti (Leksema: Jurnal Bahasa dan Sastra, 2016)
This study aims to investigate the ideology of pop culture in Esti Kinasih’s Fairish teenager literature with descriptive analytical method and is framed based on pop culture and ideology theory. The study was conducted by analyzing the representation of pop culture in the intrinsic elements of the novel and in the dialogues and narrations as well. The elements are then analyzed how they are intertwined to form a particular ideology that is injected to the readers. The result of the analysis shows that the novel contains pop culture which is visible from the colloquial language, the partyculture, the dating culture and the stereotypes of boy/girlfriend, and the idea of how to resolve the problem as well. The ideology found is the idea injection that the artificial culture –although it is outside the norm and appropriateness of Indonesian culture- constitutes something that is reasonable and legitimate to do.